Educational games: educational training through meaningful learning and a curriculum adapted by projects (Research, Society and Development, 2020)
With the development of education, it became evident the need to produce in the student, the ability to interact critically with people in their environment. With this advance, the ludic approach to teaching and didactic materials have become fundamental pedagogical tools for the teaching and learning processes, characterizing the didactic game as a helper for teachers by promoting the construction of knowledge to the student. Thus, this research was developed with the objective of analyzing the influence of the elaboration of didactic games, in the construction of scientific knowledge to the student. This work presents a qualitative methodology within an exploratory bibliographic perspective, in which the denoted data were analyzed based on the perspective of the Document Analysis Method, which consists in extracting informational elements from an original document in order to express its content in a shortened, resulting in the conversion of a primary document into a secondary document. In the data obtained it can be inferred that the use of didactic games in the teaching process contributes positively to the appropriation of concepts and corroborates with the critical and intellectual formation of the student.